Asuhan Kebidanan Pada Bayi Baru Lahir Dengan Ikterus Fisiologis Di Pmb Nurhayati Air Tiris Tahun 2024 - Safitri, Nur Adinda; Syahda, Syukrianti (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Physiological jaundice is an increase in serum unconjugated bilirubin concentrations during the first week of life. Physiological jaundice is caused by high levels of unconjugated bilirubin in the body, and also due to a lack of breast milk in the first 2-3 days after the baby is born. The aim of the research was to provide midwifery care to newborns with physiological jaundice at PMB Nurhayati Air Tiris. This research took the form of a case study, which was conducted on June 10 – June 15 2024. The results of the case study research given to Mrs. F, namely, six home visits were carried out. Of the six visits, initially the baby's skin was yellow on the face and neck and there was still little breast milk, after midwifery care was carried out in the form of providing counseling about physiological jaundice, exposing the baby to the morning sun and providing breast care. Based on the care given to Mrs. F at 3 days old found that the baby's skin was no longer yellow and there was plenty of breast milk. Thus, it can be concluded that the care provided was carried out well and produced positive results. It is hoped that the results of this case study can become a reference, add to discourse and expand knowledge regarding midwifery care for newborns with physiological jaundice.